Method for preparing hard carbon spherical material for negative electrode of high-performance sodium-ion battery
The phenolic resin-based hard carbon anode material was prepared through a solution polymerization-hydrothermal two-step method, which solved the problem of insufficient performance of existing sodium-ion battery anode materials and achieved a hard carbon material with high reversible capacity and excellent electrochemical properties.
Patent Information
- Application Number
- CN202410522590.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-28
- Publication Date
- 2025-01-21
Smart Images

Figure CN119330331A_ABST
Abstract
Description
[0001] The invention relates to the field of sodium ion batteries, and specifically uses a two-step method of solution polymerization and hydrothermal reaction to prepare a high-performance phenolic resin-derived hard carbon negative electrode. Background Art
[0002] Energy resources play a role in all aspects of society and have become a necessity in people's lives today. With the increasing demand for energy, it is urgent to find new energy resources. In recent years, the large-scale use of lithium-ion batteries has made lithium resources increasingly scarce, resulting in a sharp increase in production costs. Fortunately, sodium resources are abundant and low in cost, and sodium-ion batteries have become a promising energy storage device. Graphite is the commercial negative electrode material for lithium-ion batteries. However, commercial graphite negative electrodes cannot be used in sodium-ion batteries because it is difficult for sodium ions to form a stable embedded compound with graphite. Alloys, metal compounds and hard carbon have been used as negative electrode materials for sodium-ion batteries.
[0003] From a commercial perspective, negative electrode materials require low cost and need to provide excellent electrochemical performance. Hard carbon raw materials are abundant, low cost, and simple synthesis process, which has been favored by researchers. Hard carbon precursors are mainly divided into biomass and phenolic resin. The residual carbon rate of biomass precursors is low and the repeatability is poor. The preparation technology of phenolic resin is mature, with high carbon yield and easy to adjust structure. Phenolic resin is considered to be a precursor with industrial prospects. Patent CN201611136195 "A new method for preparing hard carbon and its application" first obtains a phenolic resin precursor by coprecipitation, then hydrothermal reaction, carbonization, and finally chemical vapor deposition to obtain hard carbon with different structures. This method involves complex and costly chemical vapor deposition technology. Patent CN113321202A "A method for preparing phenolic resin-based hard carbon microsphere material" uses spray drying to prepare phenolic resin. The rapid drying process results in insufficient cross-linking of the phenolic resin, requiring an additional pre-oxidation treatment step. In addition, the phenolic resin precursor has poor consistency due to nozzle blockage and uneven spraying. The hydrothermal method is simple to operate and the phenolic resin is evenly heated in a closed container, which helps to generate phenolic resin particles with more uniform size and morphology.
[0004] High-capacity sodium-ion batteries help to improve the energy density of batteries, which is what people have always pursued, and is conducive to the lightweight and portability of batteries. It is generally believed that the main platform capacity of sodium-ion batteries comes from the filling of sodium ions in closed pores and the embedding of sodium ions in carbon layers. In order to improve the reversible capacity of sodium-ion batteries, it is particularly important to regulate the closed-pore structure and carbon layer spacing in hard carbon materials. Cheng-yang Wang et al. published an article entitled "Properties and sodium insertion behavior of Phenolic Resin-based hard carbon microspheres obtained by ahydrothermal method" in the Journal of Electroanalytical Chemistry (755 (2015) 87–91). Phenolic hard carbon microspheres were prepared by hydrothermal method, and the carbonization temperature was controlled at 800-1500℃ to obtain the optimal platform capacity. However, there are limited methods to regulate the carbonization temperature to increase capacity. Summary of the invention
[0005] In order to overcome the above-mentioned problems, the present invention provides a simple method for preparing a phenolic resin-based hard carbon negative electrode material. A two-step solution polymerization-hydrothermal method is adopted to control the hydrothermal time and temperature to adjust the crosslinking degree of the phenolic resin, thereby adjusting the platform capacity of the phenolic-based hard carbon. The spherical phenolic resin with a high crosslinking network forms closed-pore-rich hard carbon microspheres and excellent electrochemical properties after high-temperature carbonization: high reversible capacity, good rate performance, and stable cycle performance.
[0006] The preparation steps of the phenolic resin-based hard carbon negative electrode material by the solution polymerization-hydrothermal two-step method are as follows:
[0007] Step (1) Phenol monomer, aldehyde monomer and solvent are mixed in a certain proportion, and then a catalyst is added to the system to react at a certain temperature for several hours.
[0008] After the reaction in step (2) is completed, the suspension prepared in step (1) is poured into a reaction kettle and subjected to a hydrothermal reaction at 80-300° C. for 1-24 hours to obtain phenolic resin microspheres.
[0009] Step (3) The phenolic resin microspheres obtained in step (2) are centrifuged at a rotation speed of 5000-12000 r / min, and the reaction residues are washed several times with water and ethanol.
[0010] Step (4) drying the centrifugally washed phenolic resin under normal pressure at a temperature of 60°C-80°C for 8-12 hours. After drying, phenolic resin powder is obtained. The phenolic resin powder is calcined in a tubular furnace under an inert atmosphere for 0.5-5 hours at a calcination temperature of 700-2000°C. After the calcination process is completed, phenolic resin-based hard carbon microspheres are obtained.
[0011] Preferably, the phenol monomer in step (1) is one or more of phenol, resorcinol, catechol, and hydroquinone; the aldehyde monomer is one or more of formaldehyde, benzaldehyde, acetaldehyde, propionaldehyde, glutaraldehyde, and furfural; the molar ratio of phenol to aldehyde is 1:(1-7); and the catalyst is an alkaline catalyst, accounting for 1-10% of the mass ratio of phenols.
[0012] Preferably: the reaction temperature of step (1) is 60-100°C and the reaction time is 1-5h
[0013] Preferably: the inert atmosphere in step (4) is argon or argon, and the heating rate is 2-5°C / min.
[0014] Beneficial effects of the present invention:
[0015] A method for preparing a hard carbon negative electrode with a simple preparation process, easy construction of closed pores and high sodium storage capacity is proposed. The crosslinking degree and morphology of phenolic resin are regulated by solution polymerization-hydrothermal method. After high-temperature carbonization, the three-dimensional network with high crosslinking degree helps to form a low specific surface area (<20m 2 g -1 ) and a hard carbon structure with abundant closed pores. The hard carbon with spherical morphology and large interlayer spacing prepared by this method is conducive to improving the diffusion coefficient of sodium ions in the hard carbon phase, showing a high platform capacity, excellent rate performance and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is the SEM image of the hard carbon negative electrode of Example 2
[0017] Figure 2 This is the SEM image of the hard carbon negative electrode of Comparative Example 1
[0018] Figure 3 The constant current charge and discharge curves of the hard carbon negative electrode of Example 2 and Comparative Example 1 are shown in FIG.
[0019] Figure 4 The rate curves of the hard carbon negative electrode of Example 2 and Comparative Example 1 at different current densities DETAILED DESCRIPTION
[0020] The present invention is further described below by way of specific embodiments, but is not intended to limit the present invention.
[0021] Embodiment 1:
[0022] (1) Solution polymerization: Resorcinol and benzaldehyde were mixed in a molar ratio of 1:2, poured into 100 ml of water, and 1 ml of ammonia solution was added dropwise. The reaction temperature was kept at 80°C for 2 hours. The resulting solution was called A.
[0023] (2) Hydrothermal reaction: A is then placed in a reactor for further high temperature and high pressure reaction with the temperature controlled at 150°C-1h to obtain solution B.
[0024] (3) B was centrifuged at a high speed of 10000 r / min in a centrifuge, washed with water and ethanol for 3 times each, and finally the supernatant was poured into the waste liquid to obtain a phenolic resin powder.
[0025] (4) High-temperature carbonization: The phenolic resin powder is dried at normal pressure for half a day, and then calcined in a tubular furnace under an argon atmosphere for 2 hours at a calcination temperature of 1500°C and a heating rate of 2-5°C. After the calcination process is completed, phenolic resin-based hard carbon microspheres are obtained.
[0026] Embodiment 2:
[0027] (1) Solution polymerization: Resorcinol and benzaldehyde were mixed in a molar ratio of 1:2, poured into 100 ml of water, and 1 ml of ammonia solution was added dropwise. The reaction temperature was kept at 80°C for 2 hours. The resulting solution was called A.
[0028] (2) Hydrothermal reaction: A is then placed in a reactor for further high temperature and high pressure reaction, with the temperature controlled at 150°C-3h to obtain solution B.
[0029] (3) B was centrifuged at a high speed of 10000 r / min in a centrifuge, washed with water and ethanol for 3 times each, and finally the supernatant was poured into the waste liquid to obtain a phenolic resin powder.
[0030] (4) High-temperature carbonization: The phenolic resin powder is dried at normal pressure for half a day, and then calcined in a tubular furnace under an argon atmosphere for 2 hours at a calcination temperature of 1500°C and a heating rate of 2-5°C. After the calcination process is completed, phenolic resin-based hard carbon microspheres are obtained.
[0031] Embodiment 3:
[0032] (1) Solution polymerization: Resorcinol and benzaldehyde were mixed in a molar ratio of 1:2, poured into 100 ml of water, and 1 ml of ammonia solution was added dropwise. The reaction temperature was kept at 80°C for 2 hours. The resulting solution was called A.
[0033] (2) Hydrothermal reaction: A is then placed in a reactor for further high temperature and high pressure reaction, with the temperature controlled at 150°C for 6 hours to obtain solution B.
[0034] (3) B was centrifuged at a high speed of 10000 r / min in a centrifuge, washed with water and ethanol for 3 times each, and finally the supernatant was poured into the waste liquid to obtain a phenolic resin powder.
[0035] (4) High-temperature carbonization: The phenolic resin powder is dried at normal pressure for half a day, and then calcined in a tubular furnace under an argon atmosphere for 2 hours at a calcination temperature of 1500°C and a heating rate of 2-5°C. After the calcination process is completed, phenolic resin-based hard carbon microspheres are obtained.
[0036] Embodiment 4:
[0037] (1) Solution polymerization: Resorcinol and benzaldehyde were mixed in a molar ratio of 1:2, poured into 100 ml of water, and 1 ml of ammonia solution was added dropwise. The reaction temperature was kept at 80°C for 2 hours. The resulting solution was called A.
[0038] (2) Hydrothermal reaction: A is then placed in a reactor for further high temperature and high pressure reaction, with the temperature controlled at 150°C-12h to obtain solution B.
[0039] (3) B was centrifuged at a high speed of 10000 r / min in a centrifuge, washed with water and ethanol for 3 times each, and finally the supernatant was poured into the waste liquid to obtain a phenolic resin powder.
[0040] (4) High-temperature carbonization: The phenolic resin powder is dried at normal pressure for half a day, and then calcined in a tubular furnace under an argon atmosphere for 2 hours at a calcination temperature of 1500°C and a heating rate of 2-5°C. After the calcination process is completed, phenolic resin-based hard carbon microspheres are obtained.
[0041] Embodiment 5:
[0042] (1) Solution polymerization: Resorcinol and formaldehyde were mixed in a molar ratio of 1:2, poured into 100 ml of water, and 1 ml of ammonia solution was added dropwise. The reaction temperature was kept at 80°C for 2 hours. The resulting solution was called A.
[0043] (2) Hydrothermal reaction: Place A into a reactor for further high temperature and high pressure reaction with the temperature controlled at 100°C for 1 hour to obtain solution B.
[0044] (3) B was centrifuged at a high speed of 10000 r / min in a centrifuge, washed with water and ethanol for 3 times each, and finally the supernatant was poured into the waste liquid to obtain a phenolic resin powder.
[0045] (4) High-temperature carbonization: The phenolic resin powder is dried at normal pressure for half a day, and then calcined in a tubular furnace under an argon atmosphere for 2 hours at a calcination temperature of 1500°C and a heating rate of 2-5°C. After the calcination process is completed, phenolic resin-based hard carbon microspheres are obtained.
[0046] Embodiment 6:
[0047] (1) Solution polymerization: Resorcinol and formaldehyde were mixed in a molar ratio of 1:2, poured into 100 ml of water, and 1 ml of ammonia solution was added dropwise. The reaction temperature was kept at 80°C for 2 hours. The resulting solution was called A.
[0048] (2) Hydrothermal reaction: Place A into a reactor for further high temperature and high pressure reaction with the temperature controlled at 100°C for 6 hours to obtain solution B.
[0049] (3) B was centrifuged at a high speed of 10000 r / min in a centrifuge, washed with water and ethanol for 3 times each, and finally the supernatant was poured into the waste liquid to obtain a phenolic resin powder.
[0050] (4) High-temperature carbonization: The phenolic resin powder is dried at normal pressure for half a day, and then calcined in a tubular furnace under an argon atmosphere for 2 hours at a calcination temperature of 1500°C and a heating rate of 2-5°C. After the calcination process is completed, phenolic resin-based hard carbon microspheres are obtained.
[0051] Embodiment 7:
[0052] (1) Solution polymerization: Resorcinol and formaldehyde were mixed in a molar ratio of 1:2, poured into 100 ml of water, and 1 ml of ammonia solution was added dropwise. The reaction temperature was kept at 80°C for 2 hours. The resulting solution was called A.
[0053] (2) Hydrothermal reaction: Place A into a reactor for further high temperature and high pressure reaction, with the temperature controlled at 100°C for 12 hours to obtain solution B.
[0054] (3) B was centrifuged at a high speed of 10000 r / min in a centrifuge, washed with water and ethanol for 3 times each, and finally the supernatant was poured into the waste liquid to obtain a phenolic resin powder.
[0055] (4) High-temperature carbonization: The phenolic resin powder is dried at normal pressure for half a day, and then calcined in a tubular furnace under an argon atmosphere for 2 hours at a calcination temperature of 1500°C and a heating rate of 2-5°C. After the calcination process is completed, phenolic resin-based hard carbon microspheres are obtained.
[0056] Embodiment 8:
[0057] (1) Solution polymerization: Resorcinol and formaldehyde were mixed in a molar ratio of 1:2, poured into 100 ml of water, and 1 ml of ammonia solution was added dropwise. The reaction temperature was kept at 80°C for 2 hours. The resulting solution was called A.
[0058] (2) Hydrothermal reaction: A is then placed in a reactor for further high temperature and high pressure reaction, with the temperature controlled at 150°C-12h to obtain solution B.
[0059] (3) B was centrifuged at a high speed of 10000 r / min in a centrifuge, washed with water and ethanol for 3 times each, and finally the supernatant was poured into the waste liquid to obtain a phenolic resin powder.
[0060] (4) High-temperature carbonization: The phenolic resin powder is dried at normal pressure for half a day, and then calcined in a tubular furnace under an argon atmosphere for 2 hours at a calcination temperature of 1500°C and a heating rate of 2-5°C. After the calcination process is completed, phenolic resin-based hard carbon microspheres are obtained.
[0061] Comparative Example 1: The steps are basically the same as those of Examples 1-4, except that step (2) is not performed, and the A obtained by solution polymerization is directly centrifuged, washed, dried, and then carbonized at high temperature.
[0062] Comparative Example 2: The steps are basically the same as those of Examples 5-8, except that step (2) is not performed, and the A obtained by solution polymerization is directly centrifuged, washed, dried, and then carbonized at high temperature.
[0063] The hard carbon of Examples 1-8 and Comparative Examples 1-2 were mixed with conductive carbon black and binder PVDF in a ratio of 8:1:1, and then evenly ground and added with NMP to form a slurry and coated on the copper foil. The obtained pole piece was dried in an oven at 120°C-12h, and then assembled into a CR2032 button battery. The diaphragm was a glass fiber diaphragm, the counter electrode was metallic sodium, and the electrolyte was 1mol / LNaPF6 / (EC+DEC, V:V=1:1). The constant current charge and discharge mode was used for testing in the blue electric system, and the voltage range was: 0.01-3V.
[0064] The following table is a comparison of the phenolic resin-based carbon microspheres obtained in Examples 1-8 and Comparative Examples 1-2.
[0065]
[0066]
[0067] As can be seen from Table 1, the yields of the phenolic resins prepared by the solution-hydrothermal two-step method of Examples 1-8 at 1500°C are higher than those of Comparative Examples 1-2, indicating that the crosslinking degree of the phenolic resin can be improved after hydrothermal treatment. The carbon interlayer spacing of the hard carbon of Examples 1-8 is also higher than that of Comparative Examples 1-2, indicating that the phenolic resin after hydrothermal treatment is beneficial to improving the diffusion coefficient of sodium ions and improving the rate performance.
[0068] Examples 1-4 are phenolic resins synthesized by the benzaldehyde raw material solution-hydrothermal method. It is found that the extension of the hydrothermal time increases the hard carbon yield at 1500°C and the reversible capacity also increases. This is because the crosslinking degree of the phenolic resin increases after hydrothermal treatment, resulting in an increase in the closed pores of the hard carbon. Although the phenolic resin is synthesized from formaldehyde, Examples 5-7 are the same. The reversible capacity also increases with the extension of the hydrothermal time.
[0069] Comparing Examples 7 and 8, it is found that the increase in hydrothermal temperature is also conducive to the improvement of reversible capacity. Comparing Examples 4 and 8, it can also be concluded that under the same conditions, the 1500°C yield and reversible capacity of the hard carbon derived from the phenolic resin synthesized from benzaldehyde are higher than those of the hard carbon synthesized from formaldehyde, because the phenolic resin synthesized from benzaldehyde has more benzene ring structures and a greater degree of crosslinking. After carbonization, the graphite crystallites are more disorderly stacked to form more closed pores.
[0070] Figure 3 The hard carbon negative electrode of Example 2 and Comparative Example 1 at 20 mA g -1 From the constant current charge and discharge curve comparison diagram, combined with Table 1, it can be seen that the reversible charging capacity and the first coulomb efficiency of Example 2 of the present invention are higher, and the platform capacity (voltage <0.1V) is higher. This is because the hydrothermal promotion of phenolic resin cross-linking contributes to the closed pores of its hard carbon.
[0071] Figure 1 and Figure 2 The scanning electron microscope images are respectively of the hard carbon negative electrode of Example 2 and Comparative Example 1. It can be found that the hard carbon negative electrode of Example 2 prepared by the two-step method is spherical with a size of 1-3 μm, while the hard carbon of Comparative Example 1 is in a large block morphology, which is not conducive to rate performance. Figure 4 The difference in rate performance between the two is clearly shown. The reversible capacity of the hard carbon negative electrode of Example 2 is higher than that of Comparative Example 1 at both low and high current densities, indicating that the solution polymerization-hydrothermal method can improve the rate performance of hard carbon. After a high current density, the hard carbon negative electrode of Example 2 can also recover 350 mAh g -1 The high capacity of about 2.5 nm indicates that the closed-cell filling is reversible.
[0072] The solution-hydrothermal two-step preparation method for the phenolic resin-derived hard carbon negative electrode material of the present invention has a simple preparation process, and the cross-linking degree of the phenolic resin can be regulated by controlling the time and temperature of the hydrothermal process. The advantages of the hard carbon negative electrode preparation method are introduced in detail, which is helpful for forming hard carbon microspheres and constructing closed pores, significantly improving the sodium ion diffusion coefficient, thereby enhancing the overall electrochemical performance of the battery, and having significant application value.
[0073] Some embodiments of the present invention have been described in detail above, but the present invention is not limited to the embodiments. Those skilled in the art may make equivalent modifications or substitutions without violating the spirit of the present invention. These equivalent modifications or substitutions are all included in the scope defined by the claims of this application.
Claims
1. A method for preparing a phenolic resin-based hard carbon microsphere negative electrode material, characterized in that The preparation process includes the following steps: (1) Phenol monomer, aldehyde monomer and solvent are mixed in a certain proportion, and then a catalyst is added to the system to react at a certain temperature for several hours; (2) pouring the obtained suspension into a reactor, performing a hydrothermal reaction for several hours to obtain phenolic resin microspheres, centrifuging at a speed of 5000-12000 r / min, and washing the reaction residues with water and ethanol several times; (3) drying the phenolic resin after centrifugal washing, and carbonizing it in a tube furnace under an inert atmosphere to obtain phenolic resin-based hard carbon microspheres.
2. The preparation method according to claim 1, wherein in step (1), the phenol monomer is one of phenol, resorcinol, catechol, and hydroquinone; the aldehyde monomer is one or more of formaldehyde, benzaldehyde, acetaldehyde, propionaldehyde, glutaraldehyde, and furfural; the molar ratio of phenol to aldehyde is 1: (1-7), the catalyst is an alkaline catalyst, and the mass ratio of the catalyst to the phenol is 1-10%. The reaction temperature is 60-100°C, and the reaction time is 1-5h.
3. The preparation method according to claim 1, wherein in step (2), the hydrothermal temperature is 80-300°C and the time is 1-24h.
4. The preparation method according to claim 1, wherein in step (3), the inert atmosphere is argon, the carbonization temperature can be 700-2000°C, the time is 0.5-5h, and the heating rate is 2-5°C / min.
5. Phenolic resin-based hard carbon is characterized by: The phenolic resin-based hard carbon contains the preparation method according to any one of claims 1 to 4.
6. The phenolic resin-based hard carbon according to claim 5, characterized in that: The specific surface area of the phenolic resin-based hard carbon negative electrode material is 0.1-50m 2 / g, particle size is 1 to 5 μm.
7. The phenolic resin-derived hard carbon prepared according to any one of claims 1 to 6 is used as a negative electrode material for sodium ion batteries.
Citation Information
Patent Citations
Preparation method of phenolic resin-based hard carbon microsphere material
CN113321202A
Phenolic resin-based hard carbon microspheres, preparation method thereof, negative electrode material and secondary battery
CN105914371A
Novel method for preparing hard carbon and application of novel method
CN106450320A
Phenolic resin-based spherical hard carbon negative electrode material with adjustable structure for sodium ion battery and preparation method of phenolic resin-based spherical hard carbon negative electrode material
CN115535998A
Preparation method of modified phenolic resin-based hard carbon material and sodium ion battery
CN117886299A
Cited By
Micron-sized phenolic resin carbon microspheres, and synthesis method and application thereof
CN122916111A